2020
DOI: 10.1158/2159-8290.cd-19-0463
|View full text |Cite
|
Sign up to set email alerts
|

Histone Lysine Methylation Dynamics ControlEGFRDNA Copy-Number Amplification

Abstract: Acquired chromosomal DNA copy gains are a feature of many tumors; however, the mechanisms that underpin oncogene amplifi cation are poorly understood. Recent studies have begun to uncover the importance of epigenetic states and histone lysine methyltransferases (KMT) and demethylases (KDM) in regulating transient site-specifi c DNA copy-number gains (TSSG). In this study, we reveal a critical interplay between a myriad of lysine methyltransferases and demethylases in modulating H3K4/9/27 methylation balance to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…The role of chromatin-modifying enzymes and epigenetic states in ecDNA oncogene copy number amplification is becoming apparent (Figure 3). Clarke et al 44 have elegantly demonstrated the role of histone lysine methyltransferases (KMTs) and demethylases (KDMs) in modulating histone methylation balance and subsequent transient site-specific EGFR copy gains including high-level EGFR amplification. In this work, combining public datasets with functional work in cell lines, including immortalised retinal pigment epithelial cells, they demonstrate that interference of H3K9 and H3K27 methylation states results in site-specific EGFR amplification and expression.…”
Section: The Epigenomic Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…The role of chromatin-modifying enzymes and epigenetic states in ecDNA oncogene copy number amplification is becoming apparent (Figure 3). Clarke et al 44 have elegantly demonstrated the role of histone lysine methyltransferases (KMTs) and demethylases (KDMs) in modulating histone methylation balance and subsequent transient site-specific EGFR copy gains including high-level EGFR amplification. In this work, combining public datasets with functional work in cell lines, including immortalised retinal pigment epithelial cells, they demonstrate that interference of H3K9 and H3K27 methylation states results in site-specific EGFR amplification and expression.…”
Section: The Epigenomic Landscapementioning
confidence: 99%
“…44 Furthermore, they build on previous work to demonstrate that hypoxia and epidermal growth factor (EGF) promote transient site-specific EGFR copy gains through targeting H3K4 methylation via different epigenetic means. 44,45 These data suggest that pharmacological targeting of epigenetic modifiers may attenuate extrachromosomal amplification of EGFR.…”
Section: The Epigenomic Landscapementioning
confidence: 99%
“…In the case of ovarian cancers, increased KDM4A levels associated directly with co-amplification of chromosomal region 1q12-21. Similarly, the interplay between elevated KDM4A and chromatin methylation status regulated oncogene EGFR copy gains in lung cancer cell lines and in cultured cells overexpressing KDM4A [ 72 ]. Similar observations were reported in breast cancer stem-like cells [ 73 ].…”
Section: Role Of Kdm4a In Genomic Instabilitymentioning
confidence: 99%
“…In this manner, HIF1 target genes drive pathways and biological processes that promote cancer progression. In comparison, the current knowledge of hypoxia-inducible G9a and GLP non-histone substrate methylation is less complete (Figure 5), but it is clear that lysine methylation plays a key role in affecting cancer pathways (McGrath and Trojer, 2015;Carlson and Gozani, 2016;Clarke et al, 2020). Below, we discuss similar implications regarding the G9a and GLP relevance in cancer progression, such as through hypoxia-responsive non-histone methylation.…”
Section: Hypoxic Methylation and Pathological Relevancementioning
confidence: 99%